The Tax Information Exchange Agreements and their Implementation in Peru - Valdez Ladrón de Guevara, Patricia (2014)
In this article, the author begins by giving an overview of the systems of tax information exchange. Not only describes and analyzes the nature of this figure, but also performs a comprehensive analysis of the content, the subjects involved, and the ways and means of information exchange. Finally, analyzes international agreements on exchange of information on tax matters in Peru which is part. He concludes his analysis by focusing on the implementation of FATCA (Foreingn Account Tax Compliance Act) in Peru.